A new multi-rotor UAV landing device and safety boundary assessment method - Jiejie KONG; Jianyao WANG; Hongdong WANG (Zhongguo Jianchuan Yanjiu, 2024)
ObjectiveTo solve the problem of the autonomous and safe landing of multi-rotor unmanned aerial vehicles (UAVs) in the application of unmanned platforms at sea, this paper studies multi-rotor UAV landing devices and their safety boundary assessment methods.MethodBased on the idea of the "Harpoon-Grid" rapid securing system, a new type of "V-foot–net" landing device is designed for multi-rotor UAVs. Multi-rigid body dynamic models of the UAV and deck are established, and simulations of the landing process are carried out using ADAMS under different rolling amplitudes and period conditions to obtain the attitude change process, landing critical period and attitude stabilization time of the UAV. ResultsThe simulation results show that the proposed "V-foot–net" device has higher docking redundancy under a smaller rolling period and larger rolling amplitude, and achieves attitude stability faster than ordinary landing devices.ConclusionThe results show that this device has superior safety compared to ordinary devices, and its safety boundary obtained through simulation can provide valuable references for improving the reliability of the autonomous landing of UAVs on offshore platforms.